2020
DOI: 10.1183/13993003.03546-2020
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pleural empyema in English hospitals and the impact of influenza

Abstract: Pleural empyema represents a significant healthcare burden due to extended hospital admissions and potential requirement for surgical intervention. This study aimed to assess changes in incidence and management of pleural empyema in England over the last 10 years and the potential impact of influenza on rates.Hospital Episode Statistics (HES) data was used to identify patients admitted to English hospitals with pleural empyema between 2008 and 2018. Linear regression was used to analyse the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…Parameters related to higher IET-related bleeding have been identified that may lead to altered risk thresholds for treatment. Pleural infection is rising in incidence [1][2][3] and remains associated with prolonged hospital stays and high mortality. 4 Combination intrapleural fibrinolytic and enzyme therapy (IET) with tissue plasminogen activator (tPA) and deoxyribonuclease has been established as a surgery-sparing rescue treatment option.…”
Section: Q7mentioning
confidence: 99%
“…Parameters related to higher IET-related bleeding have been identified that may lead to altered risk thresholds for treatment. Pleural infection is rising in incidence [1][2][3] and remains associated with prolonged hospital stays and high mortality. 4 Combination intrapleural fibrinolytic and enzyme therapy (IET) with tissue plasminogen activator (tPA) and deoxyribonuclease has been established as a surgery-sparing rescue treatment option.…”
Section: Q7mentioning
confidence: 99%
“…Recent national epidemiological studies of pleural infection from North America also show significant increases in pleural infection rates both in children [22] and adults [23]. Likewise, a Danish study from 1997-2001, showed steadily rising pleural infection rates in the elderly [24] and a UK study showed annual rises in adult pleural infections from 2008-17 [25], most marked in over 60-year-old individuals with a 194% increase over the decade. Both overall admissions and microbiological testing at the study hospitals increased progressively during our study period, but not as much as disease incidence, suggesting this did not solely account for the increasing incidence observed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, pre-existing medical conditions were commonly present amongst adults with pneumococcal parapneumonic effusions, although the median patient age was lower than that seen in other cohorts of parapneumonic effusions [12, 25]. Uniquely, this cohort of parapneumonic effusion cases were all attributable to pneumococcal infection, which may cause the condition in younger patients than other pathogens [25, 38]. Despite this, the burden of pre-existing medical comorbidity was equivalent: both SPE and pleural infection patients had significant cardiac (44%) and respiratory (43%) conditions predominating.…”
Section: Discussionmentioning
confidence: 99%
“…A huge rise in pleural infection cases is well documented following the influenza pandemic in 1918 [5] and a recent epidemiological study from Arnold et al also found that for 9 of the 10 years studied, the highest annual point incidence of influenza nationally coincided with the highest admission rate for pleural infection [6].…”
Section: Introductionmentioning
confidence: 92%